La Cour suprême du Canada : ses jugements récents en assurance - de Grandpré, Louis-Philippe (Assurances)

(untitled) (HEC Montréal, 1993)
Mr. Louis-Philippe de Grandpré, President of the Bar and former judge of the Supreme Court of Canada, quotes and comments on a number of recent court cases involving insurance companies versus policyholders. ln an attempt to find judicial consistency, the author finds that certain decisions are questionable and concludes with critical comments.